Rapid shelf‐wide cooling response of a stratified coastal ocean to hurricanes. Issue 6 (15th June 2017) - Seroka, Greg; Miles, Travis; Xu, Yi; Kohut, Josh; Schofield, Oscar; Glenn, Scott
Abstract: Large uncertainty in the predicted intensity of tropical cyclones (TCs) persists compared to the steadily improving skill in the predicted TC tracks. This intensity uncertainty has its most significant implications in the coastal zone, where TC impacts to populated shorelines are greatest. Recent studies have demonstrated that rapid ahead‐of‐eye‐center cooling of a stratified coastal ocean can have a significant impact on hurricane intensity forecasts. Using observation‐validated, high‐resolution ocean modeling, the stratified coastal ocean cooling processes observed in two U.S. Mid‐Atlantic hurricanes were investigated: Hurricane Irene (2011)—with an inshore Mid‐Atlantic Bight (MAB) track during the late summer stratified coastal ocean season—and Tropical Storm Barry (2007)—with an offshore track during early summer. For both storms, the critical ahead‐of‐eye‐center depth‐averaged force balance across the entire MAB shelf included an onshore wind stress balanced by an offshore pressure gradient. This resulted in onshore surface currents opposing offshore bottom currents that enhanced surface to bottom current shear and turbulent mixing across the thermocline, resulting in the rapid cooling of the surface layer ahead‐of‐eye‐center. Because the same baroclinic and mixing processes occurred for two storms on opposite ends of the track and seasonal stratification envelope, the response appears robust. It will be critical to forecast these processes and their implications for a wide range of future storms using realistic 3‐D coupled atmosphere‐ocean models to lower the uncertainty in predictions of TC intensities and impacts and enable coastal populations to better respond to increasing rapid intensification threats in an era of rising sea levels. Key Points: Observations, models reveal similar processes governing stratified coastal ocean cooling response to Hurricane Irene, Tropical Storm Barry Robust shear‐induced mixing produced rapid ahead‐of‐eye‐center cooling in TCs on opposite ends of track and seasonal stratification envelope Coupled TC models capable of predicting processes leading to rapid cooling of stratified coastal oceans critical for populated coastlines